Knowledge, attitude, and awareness (KAA) regarding water, sanitation, and hygiene (WASH) among rural residents in Kerian, Perak - Rahim, Nur Ain (Faculty of Medicine and Health Sciences, 2022)
Introduction: To study knowledge, attitude, and awareness (KAA) regarding water, sanitation, and hygiene (WASH) among rural residents in three villages in Kerian, Perak. Methods: A cross-sectional study was conducted among 165 residents aged 18 years old and above. All respondents were sampled through cluster sampling. A set of validated questionnaires from previous studies consisting of four sections were used to access the level of KAA. Data analysis was performed by using SPSS Version 22. Results: Overall, the study found that knowledge (40.0%), attitude (76.0%), awareness (59.0%) were at moderate levels. Chi-square analysis showed that there was an association between level of knowledge and household income (X2 = 20.765, p=0.004) and gender (X2 =7.263, p=0.027). However, there was no association between age and level of knowledge (X2 =8.599, p=0.335). In addition, there was a significant association between knowledge and attitude (p=0.006, r=0.211), and knowledge and awareness (p=0.009, r=0.203). Both associations showed a poor correlation between them. Conclusion: This study concludes that as knowledge level improves, so does attitude and awareness. The media plays a important role as a medium for behavioral changes communication among the community. Continuous education through health promotion programs is needed to ensure information regarding WASH is distributed fairly among the community.